2017
DOI: 10.1210/js.2017-00414
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Atezolizumab-Induced Hypophysitis

Abstract: Cancer immunotherapy has emerged as treatment of multiple advanced cancer types. Immune checkpoint inhibitors, namely anticytotoxic T-lymphocyte antigen-4 (CTLA-4), antiprogrammed cell death-1 (PD-1), and antiprogrammed cell death-1 ligand 1 (PD-L1) antibodies, have been used for treatment of various cancers. Classified as immune-related adverse events, several endocrinopathies, including hypophysitis, are associated with these agents. Although anti-CTLA-4–induced hypophysitis has been frequently observed, hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 11 publications
2
37
0
Order By: Relevance
“…Brain injury resulting from traumatic thoracic injury [4], autoimmune disease [5], and Cytotoxic T-lymphocyte antigen (CTLA)-4 is expressed in the pituitary gland; anti-CTLA-4 antibodies were reported to induce hypophysitis [7]. Furthermore, anti-programmed cell death (PD)-1 and anti-PD-ligand 1 antibodies have been reported to induce hypophysitis, leading to pituitary atrophy [8]. Therefore, we must be aware of various signs of hypopituitarism when we perform invasive dental treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Brain injury resulting from traumatic thoracic injury [4], autoimmune disease [5], and Cytotoxic T-lymphocyte antigen (CTLA)-4 is expressed in the pituitary gland; anti-CTLA-4 antibodies were reported to induce hypophysitis [7]. Furthermore, anti-programmed cell death (PD)-1 and anti-PD-ligand 1 antibodies have been reported to induce hypophysitis, leading to pituitary atrophy [8]. Therefore, we must be aware of various signs of hypopituitarism when we perform invasive dental treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that hypophysitis occurred mostly in patients treated with anticytotoxic T lymphocyte associated antigen‐4 (CTLA4) inhibitors due to CTLA‐4 expressed on pituitary cells . However, hypophysitis has also been reported in patients treated with atezolizumab or nivolumab . Hypophysitis induced by PD‐1/PD‐L1 inhibitor usually presents as isolated ACTH deficiency.…”
Section: Toxicity Profilementioning
confidence: 99%
“…The order of hormone deficiency specific to hypophysitis is as follows: ACTH > TSH > luteinizing hormone/follicle‐stimulating hormone > prolactin > growth hormone . Immune‐related hypophysitis may not affect all pituitary cell lines, and isolated ACTH deficiency has been reported …”
Section: Toxicity Profilementioning
confidence: 99%
See 2 more Smart Citations